2021
DOI: 10.3390/ani11113124
|View full text |Cite
|
Sign up to set email alerts
|

Transforming the Emotional Intelligence of the Feeders in Agribusinesses into the Development of Task Performance and Counterproductive Work Behaviors during the COVID-19 Pandemic

Abstract: The present research poses a novel multilevel model to describe how transformational leadership can significantly affect task performance and counterproductive work behavior through intermediary effects of emotional intelligence, work engagement, and work burnout. The empirical data is from 240 livestock feeders from 80 Taiwanese livestock production agribusinesses. The empirical results demonstrate that leadership could indeed transform the emotional intelligence of livestock feeders into positive task perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Therefore, ethical leadership is a significant driver of strategic adoption of the upper management team, as ethical leadership can shape the upper management team's preference for environmental ethics to influence strategic preference. Past research also supports this mechanism that both leadership and environmental strategies can improve firm performance [21,65,66].…”
Section: Academic Contributionmentioning
confidence: 75%
“…Therefore, ethical leadership is a significant driver of strategic adoption of the upper management team, as ethical leadership can shape the upper management team's preference for environmental ethics to influence strategic preference. Past research also supports this mechanism that both leadership and environmental strategies can improve firm performance [21,65,66].…”
Section: Academic Contributionmentioning
confidence: 75%
“…Innovative work practices include crafting jobs complying with health guidelines [95], motivating leader health mindset, increasing employees' perceived organizational health climate [96], and working from home [74]. Moreover, job reattachment with safety concerns [97], becoming a learning organization [98], and concern for high recovery capacity people getting work done [99] are other factors that represent innovative work practices. Concerning competency building, developing technology proficiency at home [75] is a factor of employee engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is another innovative practice facilitating work engagement as research found that learning organization drives engagement during the COVID-19 pandemic [98]. Besides, "concern for people who have high recovery capacities" (cluster 25) is another practice that can be used in driving employee engagement [99].…”
Section: Directing Employeesmentioning
confidence: 99%
“…The latent growth curve model is a modified version of the structural equation model and has been popularly used in many investigations [50][51][52]. The benefit of the latent growth curve model is to analyze variables' growth, which can confirm a causal relationship between these variables.…”
Section: Latent Growth Curve Modelmentioning
confidence: 99%